Trends in co-administration of adult vaccinations in the US retail pharmacy setting - Neha Agrawal; Alon Yehoshua; Jeffrey T. Vietri; Tianyan Hu; Taryn Pond; Maria J. Tort; Jingyan Yang; Verna Welch; Constantina Boikos; Sen Deng; Hao Zheng; Anchita Goswami; et al. (Expert Review of Vaccines)
Background Evidence on trends in co-administration of vaccines among adults is limited. This study assessed monthly trends in co-administration of US Advisory Committee on Immunization Practices (ACIP) recommended vaccines in the retail pharmacy setting and evaluated commonly co-administered vaccine combinations.Research design and methods This retrospective study used Adheris Pharmacy Dataset, including adults aged ≥ 19 years who received ≥ 1 vaccine from August 2018 to December 2023. Co-administration was defined as administration of > 1 vaccine on same day. Numbers and proportions of co-administrations were assessed by month of administration and age group. Five most commonly co-administered combinations of vaccines were identified between August 2022 and December 2023.Results Out of 161,415,432 visits with ≥ 1 vaccine administration 16,164,321 (10.0%) visits involved co-administration. Monthly co-administrations showed an upward trend from August 2018 (75,449 [11.6%]) to December 2023 (470,959 [24.0%]), with a peak in October 2023 (2,103,903 [32.6%]). Co-administration was considerably higher between September and November across the years and age groups. Influenza and COVID-19 vaccines were most commonly co-administered combination.Conclusions Most vaccination visits (~90%) were associated with single administrations, with 10% co-administrations. An increase in vaccine co-administrations was noted in 2022 and 2023 for all age groups compared to those between 2018–2021.